2006
DOI: 10.1207/s15328015tlm1802_1
|View full text |Cite
|
Sign up to set email alerts
|

APPLIED RESEARCH: Teaching Clinical Skills Through Videotape Review: A Randomized Trial of Group Versus Individual Reviews

Abstract: Although both group reviews and individual reviews of videotaped standardized patient encounters were received well by the students, there were several statistical differences in favor of the individual format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 11 publications
2
60
0
1
Order By: Relevance
“…The study showed that most students (80%) had a positive experience and found the situation less stressful than they had expected; they reported that they would not have wanted to do it in any other way. The students who had received individual feedback supported by observation of the video-recording reported a significantly higher level of satisfaction with the feedback and rated the examination as a more positive learning opportunity than did those who had received feedback in a group (17).…”
Section: Video-recording With Feedbackmentioning
confidence: 90%
“…The study showed that most students (80%) had a positive experience and found the situation less stressful than they had expected; they reported that they would not have wanted to do it in any other way. The students who had received individual feedback supported by observation of the video-recording reported a significantly higher level of satisfaction with the feedback and rated the examination as a more positive learning opportunity than did those who had received feedback in a group (17).…”
Section: Video-recording With Feedbackmentioning
confidence: 90%
“…[2][3][4][5] Medical curricula have employed innovative techniques for improving communication and assessment skills, including teaching clinical skills through videotape review, utilizing standardized video cases in assessing communication skills, and development of interactive virtual patients to improve communication and history-gathering skills. [6][7][8][9] All students in the third-professional year of the pharmacy curriculum are required to take a 3-credit Self Care 1 course in the fall semester. The Self Care 1 syllabus covers the most prevalent nonprescription topics in practice, such as herbal pharmacotherapy, fever and pain, cough and cold, gastrointestinal ailments, and home monitoring devices.…”
Section: Introductionmentioning
confidence: 99%
“…However, these benefits come with some discomforts to learners (Beckman & Cohen 1994). The previous randomized trial found that both individual and group reviews of videotaped standardized patient encounters were received well by the 4th-year medical students in the United States (Parish et al 2006). However, there was a statistically significant difference in favor of the individual review format.…”
Section: Discussionmentioning
confidence: 99%